CMet agonistic antibody prevents acute kidney injury to chronic kidney disease transition by suppressing Smurf1 and activating Smad7. Issue 11 (11th June 2021) - Li, Lilin; Lee, Jeonghwan; Cho, Ara; Kim, Jin Hyuk; Ju, Wonmin; An, Jung Nam; Park, Jeong Hwan; Zhu, Shi Mao; Lee, Junghun; Yu, Seung-Shin; Lim, Chun Soo; Kim, Dong Ki; et al.
Abstract: We aimed to investigate the role of cMet agonistic antibody (cMet Ab) in preventing kidney fibrosis during acute kidney injury (AKI) to chronic kidney disease (CKD) transition. Additionally, we explored the effect of cMet Ab on TGF-β1/Smad pathway during the pathogenesis of kidney fibrosis. A unilateral ischemia–reperfusion injury (UIRI) mouse model was established to induce AKI-to-CKD transition. Furthermore, we incubated human proximal tubular epithelial cells (hPTECs) under hypoxic conditions as in vitro model of kidney fibrosis. We analyzed the soluble plasma cMet level in patients with AKI requiring dialysis. Patients who did not recover kidney function and progressed to CKD presented a higher increase in the cMet level. The kidneys of mice treated with cMet Ab showed fewer contractions and weighed more than the controls. The mice in the cMet Ab-treated group showed reduced fibrosis and significantly decreased expression of fibronectin and α-smooth muscle actin. cMet Ab treatment decreased inflammatory markers (MCP-1, TNF-α, and IL-1β) expression, reduced Smurf1 and Smad2/3 level, and increased Smad7 expressions. cMet Ab treatment increased cMet expression and reduced the hypoxia-induced increase in collagen-1 and ICAM-1 expression, thereby reducing apoptosis in the in vitro cell model. After cMet Ab treatment, hypoxia-induced expression of Smurf1, Smad2/3, and TGF-β1 was reduced, and suppressed Smad7 was activated. Down-regulation of Smurf1 resulted in suppression of hypoxia-induced fibronectin expression, whereas treatment with cMet Ab showed synergistic effects. cMet Ab can successfully prevent fibrosis response in UIRI models of kidney fibrosis by decreasing inflammatory response and inhibiting the TGF-β1/Smad pathway.